The study of sediment behaviour changes at Sungai Lembing between 2008 and 2016 - Mohamad Aiman, Mohamad Nawawi (2017)
A study on sediment behaviour was conducted at Sungai Lembing, Kuantan. In order to determine the change of sediment properties regarding size, density and fall velocity, several related were conducted in the laboratory. Particle size distribution and total suspended solid analysis that were carried out to classify properties of the soil sample and the concentration of suspended solid. From the soil classification test, this soil is gravel soil with fine soil and silt. The second objective is to identify the change of river cross section between 2008 and 2016.The cross section of river had measure and compare. It overcome huge changes after 8 years. The exact amount rainfall intensity 2016 recorded according Malaysia average rainfall. The characteristics at Sg. Lembing required to identify because it may effect the flow of the river during a usual day and flood event. This study involve five location of study area. The sediment sample sieving test results was classified using Unified Soil Classification System (USCS). The soil classification at Sungai Lembing for every station is almost entirely classified as Poorly Graded Sands (SP) . The flow rate data also had record for every location by using propeller current metre. The highest flow rate was recorded about 8.61m³/s located at station 3. The lowest flow rate recorded is about 0.837m³/s located at Station 1.